Alternatives in local risk management in cantons without regulatory plan: case of Alajuelita - Arroyo González, Luis Nelson (Revista Geográfica de América Central., 2019)
The situation of environmental deterioration and the absence of a Regulatory Plan, has motivated the establishment of Risk Management alternatives to residents of some neighborhoods through talks, trainings, delivery of informative material and field practices. This has led to the formation of Neighborhood Emergency Committees, where the incorporation of residents has established a substantial difference in the identification, surveillance and attention of risky sites, with evident improvements in the community organization and self-care.